Soil quality index in conventional and semi-ecological farms producing plantain (Musa AAB Simmonds cv. Dominic Harton) in Anolaima-Cundinamarca, Colombia - Roberth Alberto Herrera Culma; Lina Isabel Calderón Rodríguez; Àlvaro Martìn Gutiérrez Malaxechebarría (Acta Agronómica)
This research aimed to generate a soil quality index which have allowed to compare the effect of conventional and semi-ecological plantain farming systems. For its construction, we considered biometric data of near-to-harvest plants, physical, chemical and biological indicators which were evaluated using a principal components analysis; the weight of each indicator was calculated, and so were the response curves, establishing a minimum set of data which includes: sand percentage, sheet of water, pH, Nitrogen, organic carbon percentage, potassium, biodiversity conservation and microbial respiration, respectively. In fact, this index was validated in areas cultivated with plantain cv. Dominic Harton in farms located in the same taxonomic unit in Anolaima-Cundinamarca, Colombia. Results indicate that farms with semi-ecological practices had achieved a better soil quality than those with conventional practices.